The selective cytotoxicity of DSF-Cu attributes to the biomechanical properties and cytoskeleton rearrangements in the normal and cancerous nasopharyngeal epithelial cells. (March 2017) - Yang, Yaping; Li, Mengjia; Sun, Xiaoxue; Zhou, Congran; Wang, Yawei; Wang, Liwei; Chen, Lixin; Liang, Zhihong; Zhu, Linyan; Yang, Haifeng
Abstract: Cancer initiation and progression follow complex changes of cellular architecture and biomechanical property. Cancer cells with more submissive (or "softer") than their healthy counterparts attributed to the reorganization of the complex cytoskeleton structure, may be considered as a potential anti-tumor therapeutic target. In this study, atomic force microscopy (AFM) was carried out to detect the topographical and biophysical changes of nasopharyngeal carcinoma CNE-2Z cells and normal nasopharyngeal epithelial cells NP69-SV40T by treating the Disulfiram chelated with Cu 2+ (DSF-Cu). DSF-Cu induced the apoptotic population, ROS production and decreased the NF-κB-p65 expression of CNE-2Z cells, which was much higher than those of NP69-SV40T cells. DSF-Cu caused the obvious changes of cell morphology and membrane ultrastructure in CNE-2Z cells. The roughness decreased and stiffness increased significantly in CNE-2Z cells, which correlated with the rearrangement of intracellular F-actin, FLNa and α-tubulin structures in CNE-2Z cells. And the adhesion force of CNE-2Z cells was also increased accompanied with the increased E-cadherin expression. However, these results could not be observed in the NP69-SV40T cells even the concentration of DSF reached up to 400 nM. Finally, the detection of cell wound scratch assay confirmed DSF-Cu could inhibit the migration of CNE-2Z cells, but no effect on NP69-SV40T cells. These findings demonstrated the selective cytotoxicity of DSF-Cu in CNE-2Z cells may attribute to the different mechanical properties and cytoskeleton rearrangement from the normal nasopharyngeal epithelial cells.